The mastic tree (Pistacia lentiscus L.) leaves as source of BACs effect of growing location, phenological stage and extraction solvent on phenolic content - Dragović, Sanja, inženjerka bioprocesnog inženjerstva; Dragović-Uzelac, Verica; Pedisić, Sandra; Čošić, Zrinka; Friščić, Maja, magistra farmacije; Elez Garofulić, Ivona; Zorić, Zoran, kemičar (2020)
Research background. Mastic tree (Pistacia lentiscus L.) of the Anacardiaceae family is an evergreen shrub from Mediterranean countries where it is used in traditional medicine. Analysis of P. lentiscus leaf, stem, fruit and root extracts showed high concentrations of principal groups of secondary metabolites (flavonoids, phenolic acids and tannins), suggesting the plant possesses great biological potential. Therefore, the aim of this research is to evaluate the impact of environmental parameters and the extraction solvent type on the concentration of phenols in mastic tree leaf extracts grown at four different locations along the Adriatic coast (Barbariga, Lun, Hvar and Vela Luka) during three phenological stages (early flowering, early fruiting and late fruiting).Experimental approach. Since mastic tree plant has phenolic compounds with different structures and chemical properties, ethanolic and methanolic leaf extracts were analysed using high-performance liquid chromatography (HPLC) coupled with UV/Vis PDA detector. Phenolic compounds were identified by comparing the retention times and spectral data with those of standards at 280 and 340 nm.Results and conclusions. In all samples, phenolic acids and flavonol glycosides were quantified, while catechin was quantified only in methanolic extracts. The 5-O-galloylquinic acid was determined as a predominant phenolic compound in all samples followed by monogalloyl glucose, 3,5-di-O-galloylquinic acid, 3,4,5-tri-O-galloylquinic acid and gallic acid, respectively. Myricetin-3-O-rhamnoside was found to be the predominant flavonol glycoside followed by myricetin-3-O-glucoside, myricetin-3-O-glucuronide, quercetin-3-O-rhamnoside and derivative of flavonol glycoside. The mass concentration of these compounds significantly varied during different phenological stages, at different growing locations and used extraction solvents.
Pozadina istraživanja. Tršlja (Pistacia lentiscus L.) je zimzeleni grm iz porodice Anacardiaceae, rasprostranjen u mediteranskim zemljama, gdje se koristi u narodnoj medicini. Dosadašnja istraživanja ekstrakata lista, stapke, ploda i korijena P. lentiscus pokazuju da biljka sadržava veliku koncentraciju sekundarnih metabolita (flavonoida, fenolnih kiselina i tanina), što upućuje na zaključak da ima izvrstan biološki potencijal. Stoga je svrha ovoga rada bila procijeniti utjecaj okolišnih čimbenika i vrste ekstrakcijskog otapala na koncentraciju fenola u listu tršlje uzgojene na četiri različite lokacije duž Jadranske obale (Barbariga, Lun, Hvar i Vela Luka) tijekom tri fenološke faze (faze cvatnje, ranog ploda i zrelog ploda). Eksperimentalni pristup. Budući da listovi tršlje sadržavaju fenolne spojeve koji se razlikuju po strukturi i kemijskim svojstvima, ispitivanje etanolnih i metanolnih ekstrakata provedeno je visokodjelotvornom tekućinskom kromatografijom (HPLC) s UV-Vis PDA detektorom. Fenolni spojevi su identificirani usporedbom retencijskih vremena i dobivenih spektara s odgovarajućim standardima pri 280 i 340 nm. Rezultati i zaključci. U svim su uzorcima određene koncentracije fenolnih kiselina i flavonol glikozida, dok je koncentracija katehina određena samo u metanolnim ekstraktima. Prevladavajući fenolni spoj bila je 5-O-galoilkininska kiselina, zatim su slijedili monogaloil-glukoza, 3,5-di-O-galoilkininska kiselina, 3,4,5-tri-O-galoilkininska kiselina i galna kiselina. Dominantni flavonol glikozid bio je miricetin-3-O-ramnozid, zatim miricetin-3-O-glukozid, miricetin-3-O-glukuronid, kvercetin-3-O-ramnozid i derivat flavonol glikozida. Rezultati pokazuju da masene koncentracije navedenih spojeva variraju ovisno o fenološkoj fazi, lokaciji i korištenom otapalu. Najveće masene koncentracije fenola utvrđene su u uzorcima lista tršlje ubranim na lokaciji Hvar te ekstrahiranim s 80 %-tnom otopinom metanola.
Bibliografija: 43 jed.
Summary ; Sažetak.
Keywords: Tršlja -- Pistacia lentiscus L. -- Listovi tršlje -- Fenoli -- Ekstrakcijsko otapalo